PRAKTEK GALA UMONG (GADAI SAWAH) DALAM PERSPEKTIF SYARI'AH (STUDI KASUS DI DESA GAMPONG DAYAH SYARIF KECAMATAN MUTIARA KABUPATEN PIDIE PROVINSI ACEH) - Safrizal Safrizal (Universitas Islam Negeri Ar-Raniry, 2016)
Gala umong (pawn) has been practiced among Acehnese society until nowadays, whether in urban or rural areas. This research is aimed at seeing whether the practice of gala umong among acehnese society fulfills the requirements of Islamic shari’a. The result of the study shows that the practice of rice field pawn seing through the Islamic pillars and requirement son pawn has not met the terms of the pillars and rahnor pawn. The unfulfill practice of pawn can be seen that the unclear statement of the returning deadline that must be conduted by the user. It creates the misunderstandings amongst the parties which finally bring about the hostility among societal members. Another thing which is not in accordance with the rules is that the contract of rahnor utilization of Marhuun (collateral), in this case is a productive rice land which is used by the murtahin (pawn recipient). If it is neglected, then the ricest men will use their wealth only for the sake of getting guarantee pawm from the poor for the ongoing investment. As a result, the poor will be more poor as they could not utilize their productive wealth and the ricest will be more rice as plentiful harvest marhūn utilize. Thus, the practice of gala umong which is practiced at Dayah Sharif village, Pidie sub-district, Aceh province, is not in accordance with Shariah.